Development Strategies of Paddy Dayang Rindu Variety at Musi Rawas Regency - Septiana, Anisah; Riswani, Riswani; Yunita, Yunita (Eduvest - Journal of Universal Studies, 2025)
This research aims to analyze the appropriate strategy to be used by Dayang Rindu rice farmers in Musi Rawas Regency in rice farming and at the same time analyze the influence of production factors on production results. This research uses qualitative analysis techniques in the form of SWOT analysis and quantitative analysis techniques in the form of multiple regression analysis. The research results show that the average total income earned by farmers is 68.5 million rupiah in one production period. The results of multiple regression analysis show that the pesticide variable has an insignificant and negative influence. The seed variable has a positive but not significant effect, while the land area, fertilizer and labor variables have a positive and significant effect on the production results of dayang rindu longing. The results of the SWOT analysis place the Dayang Rindu rice farming business in Quadrant I, which means the strategy to be used is to strengthen internal advantages by optimizing land use to increase productivity levels. Another strategy is to build collaboration with local governments and financial institutions to open opportunities and create capabilities in marketing agricultural products.